Antecedents of Smartphone Purchase Intention - Mardhotillah, Safira Hanief; Khoerunnisa, Bentang; Curatman, Aang (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: The objective of this study is to examine and explain (1) how brand image affects purchase intention and (2) how brand image affects customer satisfaction. (3) how purchase intention is impacted by customer satisfaction; (4) how purchase intention is impacted by online customer reviews (5) Customer satisfaction acts as a mediator in the link between purchase intention and brand image. Design/methodology/approach: A quantitative method was utilized for data collection via the distribution of surveys. The sample size for the study was established based on the guidelines provided by Hair et al. (7x25) method for sampling, which involved the selection of 175 respondents. The selection of respondents was guided by criteria pertinent to the study's objectives. The study employed a 5 Likert scale to assess respondents' perceptions and responses to the proposed statements, thereby providing a quantitative metric for the study's outcomes. Findings: A quantitative method was utilized for data collection via the distribution of surveys. The sample size for the study was established based on the guidelines provided by Hair et al. (7x25) method for sampling, which involved the selection of 175 respondents. The selection of respondents was guided by criteria pertinent to the study's objectives. The study employed a 5 Likert scale to assess respondents' perceptions and responses to the proposed statements, thereby providing a quantitative metric for the study's outcomes. Research limitations/implications: The present study is subject to certain limitations, including its exclusive focus on data from the Cirebon Regency and City. Practical implications: Structural Equation Modeling (SEM) using Smart Partial Least Squares (Smart PLS) software was used to do a testing study. Originality/value: This paper is. Paper type: Research paper